If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-85-(-60)/5(5-6)=x
We move all terms to the left:
-85-(-60)/5(5-6)-(x)=0
We add all the numbers together, and all the variables
-x-85-(-60)/5(-1)=0
We add all the numbers together, and all the variables
-1x-85-(-60)/5(-1)=0
We multiply all the terms by the denominator
-1x*5(-1)-85*5(-1)-(-60)=0
We add all the numbers together, and all the variables
-1x*5(-1)+485=0
Wy multiply elements
-5x^2(-+485=0
We use the square of the difference formula
-5x^2(-485=0
| b=10-4. | | 32/15=19.2/x | | 8-5x-11=7 | | C=1150+n | | 3(x-1)=2(1+2x) | | 5(2x-3)=(2x+x)(8-4) | | 1.92×x/1.6×0.8=3/2 | | 3q*2-10Q+60=0 | | 5x-13=78 | | 7(x-1)+8=5(7-x)+14 | | 7(x+1)+8=5(7-x)+14 | | 2/4=q/48 | | 58=-x/9 | | 11÷5y-60=y | | .219=0.00008x+0.2072 | | 4g-13=2g+51= | | -24=6yy= | | 5.7/3.6=x/3.2 | | 27=-u/2u= | | 6m+17/2=13 | | .219=(8)(10^-5)x+0.2072 | | 4y-16=2y-12 | | (x^2-8)(4-x)=0 | | 9k^2-12k+8k=0 | | (3x^2+4)-(2x+3)=0 | | 3*(y-1)=2(y-6) | | 7(x+16)=175 | | 9(t-3)=5(2t-1) | | 7m+4=23 | | 7m=4=23 | | 3m-2/7=2m-5 | | 8p-4=4p+4 |